Responsive Law and Progressive Law: Examining the Legal Ideas of Philip Nonet, Philip Selznick, and Sadjipto Raharjo - Sukmana, Teja; Ashari, Zahrah Salsabillah; Darmawan , Yadi (Pustaka Peradaban, 2023)
Responsive Law and Progressive Law are two relevant approaches in legal studies developed by legal thinkers such as Philip Nonet, Philip Selznick, and Sadjipto Raharjo. These approaches offer different perspectives on understanding and applying the law in a constantly changing social context. Despite having different perspectives, both Progressive Law and Responsive Law share the same goal of creating a more just and relevant legal system in a social context. This paper aims to examine the ideas of Philip Nonet, Philip Selznick, and Sadjipto Raharjo regarding Responsive Law and Progressive Law. Through this examination, it is expected to reveal the differences, similarities, and contributions of each thinker to the development of more inclusive, adaptive, and just legal thinking in an evolving social context.